2013
DOI: 10.1371/journal.pone.0054241
|View full text |Cite
|
Sign up to set email alerts
|

Association of Common Mental Disorders and Quality of Life with the Frequency of Attendance in Slovenian Family Medicine Practices: Longitudinal Study

Abstract: BackgroundMost research on frequent attendance has been cross-sectional and restricted to one year attendance rates. A few longitudinal studies suggest that frequent attendance is self-limiting. Frequent attenders are more likely to have social and psychiatric problems, medically unexplained physical symptoms, chronic somatic diseases (especially diabetes) and are prescribed more psychotropic medication and analgesics.Research QuestionTo describe the attendance rates in a longitudinal study and to test if depr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 12 publications
2
26
0
Order By: Relevance
“…Lastly, users with high self‐initiated consultation rates showed a higher probability of suffering from subclinical affective symptomatology. Our study supported previous results that showed a higher degree of psychological distress (Norton et al., 2012; Vedsted et al., 2001) or anxiety/depression (Kersnik, Svab, & Vegnuti, 2001; Rifel et al., 2013; Sheehan et al., 2003; Smits et al., 2014) among frequent attenders.…”
Section: Discussionsupporting
confidence: 92%
“…Lastly, users with high self‐initiated consultation rates showed a higher probability of suffering from subclinical affective symptomatology. Our study supported previous results that showed a higher degree of psychological distress (Norton et al., 2012; Vedsted et al., 2001) or anxiety/depression (Kersnik, Svab, & Vegnuti, 2001; Rifel et al., 2013; Sheehan et al., 2003; Smits et al., 2014) among frequent attenders.…”
Section: Discussionsupporting
confidence: 92%
“…Usually, consultations with frequent attenders decreased after one year. Overall, 40% of frequent attenders continued to be frequent attenders the following year and 20% continued for two years (Rifel et al, 2013).…”
Section: Uses Of the Conceptmentioning
confidence: 95%
“…Men's consultations increased at an even older age. In addition to older age, frequent attenders were also characterised by lower levels of education (Jyväsjärvi et al, 2001;Kersnik et al, 2001;Little et al, 2001;Vedsted and Olesen, 2005;Al-Kandari et al, 2008;Robles et al, 2009;Koskela et al, 2010;Gili et al, 2011;Norton et al, 2012;Gomes et al, 2013;Rifel et al, 2013;Kaattari et al, 2015;Patel et al, 2015;Jørgensen et al, 2016).…”
Section: The Patient's Individual Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…More specifically, most publications in the field of frequent attendance are restricted to a cross-sectional design [1,11]. There is a lack of studies analyzing the phenomenon of frequent attendance using longitudinal data [8,12,13]. Using longitudinal data is important to tackle the issue of unobserved heterogeneity (e.g., genetic disposition) and to gain insights into intraindividual changes over time (e.g., changes within individuals over time from non-frequent attendance to frequent attendance).…”
Section: Introductionmentioning
confidence: 99%